Strategic Management and Public Service Innovation - Priyo Utomo; Agus Efendi; Rey Suwigtyo; Rohmah kurniawati; Wahyu Ari Andfriyanto (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Purpose: This study aims to analyze the development of research on strategic management and public service innovation in the public sector during 2020–2026. Design/methodology/approach: The study applies a Systematic Literature Review (SLR) based on PRISMA guidelines and bibliometric analysis using VOSviewer. A total of 847 articles indexed in international databases were examined to identify research trends, thematic clusters, and research gaps. Findings: The results show that public service innovation is closely linked to digital transformation, strategic leadership, collaborative governance, and organizational capabilities in managing change. Research at the municipal government level, especially in developing countries, remains limited Research limitations/implications: The study only includes articles indexed in international databases within the 2020–2026 period, which may exclude relevant studies from local or non-indexed sources. Practical implications: The findings provide guidance for policymakers and public sector managers in designing innovation-oriented strategic management practices to improve public service quality and responsiveness. Originality/value: This study integrates strategic management and public service innovation perspectives through combined SLR and bibliometric approaches. Paper type: Systematic Literature Review and bibliometric study